Cement-based capillary crystalline repair material as well as preparation method and application thereof

By developing a type of cement -based penetration of crystalline repair materials, combined with the characteristics of the ingredients and the needs of concrete structure repair materials in combination with cement base penetration, waterproof materials, solve the existing materials in terms of liquidity, adhesion performance, durability and penetration performance of liquidity, bonding performance, durability and penetration performance. Insurance has achieved efficient repair and performance improvement of concrete structures.

CN119330683APending Publication Date: 2025-01-21SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411511571.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing concrete structural repair materials have shortcomings in terms of fluidity, bonding performance, durability and permeability, resulting in unsatisfactory repair results and poor compatibility with concrete substrates, affecting the long-term performance of repair materials.

Method used

Develop a cement-based permeable crystalline repair material, which is reasonably formulated to include water, Portland cement, quartz sand, fly ash, calcium formate, magnesium oxide, silica sol, water-absorbent polymer resin, sodium hexametaphosphate, ethanol The composition of disodium diamine tetraacetate and redispersible latex powder has good fluidity and penetration properties, and has excellent bonding properties and compatibility with the concrete matrix.

Benefits of technology

The repair material can effectively improve the anti -penetration performance and durability of the concrete structure, significantly improve the mechanical properties and repair effects of the concrete structure, form a relatively complete whole, and extend the service life of the concrete structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330683A_ABST
    Figure CN119330683A_ABST
Patent Text Reader

Abstract

The invention discloses a cement-based capillary crystalline repair material as well as a preparation method and application thereof. The cement-based permeable crystallization type repairing material is prepared from the following components in parts by weight: 600 to 660 parts of water, 1000 to 1100 parts of Portland cement, 45 to 50 parts of quartz sand, 18 to 20 parts of fly ash, 50 to 55 parts of calcium formate, 30 to 33 parts of magnesium oxide, 100 to 110 parts of silica sol, 0.8 to 0.88 part of water-absorbent polymer resin, 0.8 to 0.88 part of sodium hexametaphosphate, 10 to 11 parts of disodium ethylene diamine tetraacetate and 50 to 55 parts of redispersible latex powder. The repairing material disclosed by the invention combines the component characteristics of a cement-based capillary crystalline waterproof material and the requirements of a concrete structure repairing material, has good flowability, is environment-friendly, non-toxic and odorless, has good compatibility and bonding performance with a concrete matrix, and has excellent repairing performance and bonding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of civil engineering materials, and in particular to a cement-based permeable crystallization repair material and a preparation method and application thereof. Background Art

[0002] Concrete is one of the most widely used and versatile building structural materials, with roles and functions that cannot be replaced by other materials. However, during the service of concrete structures, due to various factors, the concrete structure will inevitably crack, resulting in reduced bearing capacity and durability of the building structure, and even causing the structure to be damaged before reaching the design bearing capacity, thereby affecting the safety performance of the entire building structure and increasing the probability of engineering accidents. Therefore, timely repair of damaged and cracked concrete structures can ensure the safety and reliability of the building structure during use.

[0003] Damaged or cracked concrete structures are usually repaired with repair materials. The repair effect is not only related to the construction technology, but more importantly, it depends on the characteristics of the repair materials. According to the characteristics of the repair materials, the repair materials used to repair concrete structures are mainly the following: inorganic modified cement-based repair materials, organic polymer repair materials, and polymer and inorganic composite repair materials. Among them, cement-based materials and polymer / epoxy resins are the most widely used repair materials. However, organic polymer repair materials have high economic costs, polymers are prone to aging, and the thermal expansion coefficient is quite different from that of inorganic substrates in concrete repairs. They are not suitable for large-scale application in engineering. Organic and inorganic composite repair materials have the same problems. Although inorganic repair materials are low in cost and easy to construct, they have a long curing time and low bonding strength with the substrate. In addition, the high viscosity of the repair materials used to maintain the concrete surface makes it difficult for them to penetrate into the concrete cracks.

[0004] In view of the problems existing in the above-mentioned concrete structure repair materials, in order to enable the damaged concrete structure to obtain good repair performance and to avoid engineering accidents caused by the degradation of concrete structure performance due to the development of cracks, it is imperative to develop new concrete structure repair materials. Summary of the invention

[0005] The purpose of the present invention is to provide a cement-based penetrating crystallization repair material and a preparation method and application thereof. The cement-based penetrating crystallization repair material has good fluidity, mechanical properties, durability and permeability, has excellent bonding properties and compatibility with the concrete matrix to be repaired, and can effectively improve the waterproof performance and durability of the concrete structure.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] On the one hand, the present invention provides a cement-based permeable crystalline repair material, which includes, by weight, 600-660 parts of water, 1000-1100 parts of Portland cement, 45-50 parts of quartz sand, 18-20 parts of fly ash, 50-55 parts of calcium formate, 30-33 parts of magnesium oxide, 100-110 parts of silica sol, 0.8-0.88 parts of water-absorbent polymer resin, 0.8-0.88 parts of sodium hexametaphosphate, 10-11 parts of disodium ethylenediaminetetraacetate and 50-55 parts of redispersible latex powder.

[0008] As a preferred embodiment, the silicate cement is 42.5 ordinary silicate cement.

[0009] As a preferred embodiment, the particle size of the quartz sand is 80-120 meshes.

[0010] As a preferred embodiment, the silica sol is an alkaline nano-scale silica solution;

[0011] Preferably, the silica sol has a silicon dioxide content of 30±1%, a pH of 9 to 10.5, and a particle size of 10 to 20 nm.

[0012] As a preferred embodiment, the water-absorbing polymer resin is a polyacrylate resin, such as sodium polyacrylate resin;

[0013] Preferably, the particle size of the water-absorbent polymer resin is 60-100 meshes.

[0014] As a preferred embodiment, the redispersible latex powder is ethylene-vinyl acetate copolymer.

[0015] In another aspect, the present invention provides a method for preparing the above-mentioned cement-based permeable crystallization repair material, comprising the following steps:

[0016] (1) stirring the dry powder raw materials in the cement-based permeable crystalline repair material composition uniformly, adding water and continuing to stir;

[0017] (2) Add silica sol and stir rapidly.

[0018] As a preferred embodiment, in step (1), the stirring is revolution 65±5r / min and rotation 145±5r / min;

[0019] Preferably, the stirring time is 2 to 4 minutes;

[0020] Preferably, the stirring time is 2 to 3 minutes.

[0021] As a preferred embodiment, in step (2), the rapid stirring is revolution 130±5r / min and rotation 290±5r / min;

[0022] Preferably, the stirring time is 2 to 5 minutes.

[0023] In another aspect, the present invention provides the use of the above-mentioned cement-based permeable crystalline repair material in concrete repair;

[0024] Preferably, the invention is used in the repair of cracked and / or damaged concrete or in the reinforcement of concrete.

[0025] In the technical solution of the present invention, the cement-based permeable crystallization repair material includes active chemical components (sodium hexametaphosphate, disodium ethylenediaminetetraacetic acid, redispersible latex powder), calcium ion compensator (calcium formate), silicate compensator (silica sol), expansion component (magnesium oxide), mineral additive (fly ash), shrinkage inhibition component (water-absorbent polymer resin), etc. The repair material prepared from the above composition can be directly applied to the surface and cracks of the concrete structure by smearing, and penetrate into the interior of the concrete structure along the cracks, thereby improving the impermeability and durability of the concrete structure, thereby repairing the cracks and damaged positions of the damaged concrete structure.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] The repair material of the present invention combines the component characteristics of cement-based penetrating crystallization waterproof material and the requirements of concrete structure repair material, has good fluidity, is environmentally friendly, non-toxic, odorless, has good compatibility and bonding properties with the concrete matrix, and has excellent repair performance and bonding performance.

[0028] The cement-based permeable crystallization repair material of the present invention can be directly applied to the surface of a concrete structure, and can improve the anti-seepage performance of the concrete structure when applied to the surface of the concrete structure; when applied to repairing damaged and cracked concrete structures, it exhibits excellent permeability and repair performance, exhibits good permeable crystallization behavior at the cracks, and has good bonding performance and compatibility with the damaged concrete matrix, and can obtain a concrete whole with improved mechanical properties and durability. The repaired cracks form a relatively complete whole with the damaged matrix, and good working performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1-2 They are respectively the flexural failure of the damaged concrete specimen after being repaired with the cement-based penetrating crystalline repair material in Example 1 of the present invention and the penetration behavior diagram of the cement-based penetrating crystalline repair material at the crack.

[0030] Figure 3 The mechanical properties of the damaged concrete after the cement-based penetrating crystallization repair material in Example 2 of the present invention is directly applied to the damaged concrete surface and the cracks are repaired.

[0031] Figure 4 The frost resistance of concrete is shown when the cement-based penetrating crystallization repair material in Example 3 of the present invention is directly applied to an undamaged concrete surface. DETAILED DESCRIPTION

[0032] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0033] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0034] Example 1

[0035] The cement-based permeable crystallization repair material in this embodiment includes, by weight:

[0036] 600 parts of water, 1000 parts of 42.5 ordinary Portland cement, 45 parts of quartz sand (particle size is 100 mesh), 18 parts of fly ash, 50 parts of calcium formate, 30 parts of magnesium oxide, 100 parts of silica sol (silicon dioxide solution: mass fraction is 30%, pH is 9.5, particle size is 15nm, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.8 parts of water-absorbent polymer resin (sodium polyacrylate with a particle size of 80 mesh, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.8 parts of sodium hexametaphosphate, 10 parts of disodium ethylenediaminetetraacetate, 50 parts of redispersible latex powder (ethylene-vinyl acetate copolymer, the molar ratio of ethylene and vinyl acetate is 1:1, purchased from Shandong Yousuo Chemical Co., Ltd.).

[0037] In this embodiment, the specific steps of preparing the above composition into a cement-based permeable crystallization repair material are as follows:

[0038] (1) Weigh the dry powder raw materials according to the proportion, pour them into a stirring pot, stir slowly for 2 minutes at a speed of 65 r / min and 145 r / min, then add water and continue stirring for 2 minutes;

[0039] (2) The stirring speed is increased to a high-speed stirring state of 130 r / min for revolution and 290 r / min for rotation, and silica sol is added. Since silica sol reacts rapidly with calcium ions in the matrix material to generate white precipitate, rapid stirring is not suitable for dispersing the white precipitate. Therefore, rapid stirring is maintained after adding silica sol, and stirring is stopped after 3 minutes. The preparation of cement-based penetrating crystalline repair material is completed.

[0040] The cement-based permeable crystalline repair material prepared in this embodiment can be directly applied to the concrete surface and cracks in a smearing manner to repair damaged and cracked concrete structures, thereby improving the impermeability and durability of the concrete structure.

[0041] Example 2

[0042] The cement-based permeable crystallization repair material in this embodiment includes, by weight:

[0043] 660 parts of water, 1100 parts of 42.5 ordinary Portland cement, 50 parts of quartz sand (particle size is 110 mesh), 20 parts of fly ash, 53 parts of calcium formate, 33 parts of magnesium oxide, 110 parts of silica sol (silicon dioxide solution: mass fraction is 30%, pH is 9.5, particle size is 15nm, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.88 parts of water-absorbent polymer resin (sodium polyacrylate with a particle size of 80 mesh, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.88 parts of sodium hexametaphosphate, 11 parts of disodium ethylenediaminetetraacetic acid, 55 parts of redispersible latex powder (ethylene-vinyl acetate copolymer, purchased from Shandong Yousuo Chemical Co., Ltd.).

[0044] The specific steps and application process of preparing the above composition into a cement-based permeable crystallization repair material in this embodiment are the same as those in Embodiment 1.

[0045] Example 3

[0046] The cement-based permeable crystallization repair material in this embodiment includes, by weight:

[0047] 620 parts of water, 1033 parts of 42.5 ordinary Portland cement, 47 parts of quartz sand (particle size is 100 mesh), 18 parts of fly ash, 51 parts of calcium formate, 31 parts of magnesium oxide, 103 parts of silica sol (silicon dioxide solution: mass fraction is 30%, pH is 9.5, particle size is 15nm, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.83 parts of water-absorbent polymer resin (sodium polyacrylate with a particle size of 80 mesh, purchased from Shandong Yousuo Chemical Co., Ltd.), 0.83 parts of sodium hexametaphosphate, 10 parts of disodium ethylenediaminetetraacetic acid, 51 parts of redispersible latex powder (ethylene-vinyl acetate copolymer, purchased from Shandong Yousuo Chemical Co., Ltd.).

[0048] The specific steps and application process of preparing the above composition into a cement-based permeable crystallization repair material in this embodiment are the same as those in Embodiment 1.

[0049] Figure 1-2 They are respectively a diagram showing the flexural failure of a damaged concrete specimen repaired by the cement-based penetrating crystalline repair material in Example 1 of the present invention and a diagram showing the penetration behavior of the cement-based penetrating crystalline repair material at the crack.

[0050] Figure 3 The mechanical properties of the damaged concrete after the cement-based penetrating crystallization repair material in Example 2 of the present invention is directly applied to the damaged concrete surface and the cracks are repaired.

[0051] Figure 4 The frost resistance of concrete is shown when the cement-based penetrating crystallization repair material in Example 3 of the present invention is directly applied to an undamaged concrete surface.

[0052] from Figure 1-4 It can be seen that the cement-based permeable crystalline repair material of the present invention has good fluidity and permeability, good bonding performance and compatibility with concrete, good repair performance for damaged concrete structures, and can effectively improve the impermeability and durability of concrete structures.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cement-based permeable crystallization repair material, characterized in that: Calculated in parts by weight, it includes 600-660 parts of water, 1000-1100 parts of Portland cement, 45-50 parts of quartz sand, 18-20 parts of fly ash, 50-55 parts of calcium formate, 30-33 parts of magnesium oxide, 100-110 parts of silica sol, 0.8-0.88 parts of water-absorbent polymer resin, 0.8-0.88 parts of sodium hexametaphosphate, 10-11 parts of disodium ethylenediaminetetraacetate and 50-55 parts of redispersible latex powder.

2. The cement-based permeable crystallization repair material according to claim 1, characterized in that: The silicate cement is 42.5 ordinary silicate cement.

3. The cement-based permeable crystallization repair material according to claim 1, characterized in that: The particle size of the quartz sand is 80-120 meshes.

4. The cement-based permeable crystallization repair material according to claim 1, characterized in that: The silica sol is an alkaline nano-scale silicon dioxide solution; Preferably, the silica sol has a silicon dioxide content of 30±1%, a pH of 9 to 10.5, and a particle size of 10 to 20 nm.

5. The cement-based permeable crystallization repair material according to claim 1, characterized in that: The water-absorbing polymer resin is a polyacrylic acid salt resin; Preferably, the particle size of the water-absorbent polymer resin is 60-100 meshes.

6. The cement-based permeable crystallization repair material according to claim 1, characterized in that: The redispersible latex powder is ethylene-vinyl acetate copolymer.

7. The method for preparing the cement-based permeable crystallization repair material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) stirring the dry powder raw materials in the cement-based permeable crystalline repair material composition uniformly, adding water and continuing to stir; (2) Add silica sol and stir rapidly.

8. The preparation method according to claim 7, characterized in that: In step (1), the stirring is revolution 65±5 r / min and rotation 145±5 r / min; Preferably, the stirring time is 2 to 4 minutes; Preferably, the stirring time is 2 to 3 minutes.

9. The preparation method according to claim 7, characterized in that: In step (2), the rapid stirring is revolution 130±5r / min and rotation 290±5r / min; Preferably, the stirring time is 2 to 5 minutes.

10. Use of the cement-based permeable crystallization repair material according to any one of claims 1 to 6 in concrete repair; Preferably, the invention is used in the repair of cracked and / or damaged concrete or in the reinforcement of concrete.